Oral administration of GW788388, an inhibitor of transforming growth factor beta signaling, prevents heart fibrosis in Chagas disease. - Fabiane L de Oliveira; Tania C Araújo-Jorge; Elen M de Souza; Gabriel M de Oliveira; Wim M Degrave; Jean-Jacques Feige; Sabine Bailly; Mariana C Waghabi (Public Library of Science (PLoS), 2012)
BACKGROUND: Chagas disease induced by Trypanosoma cruzi (T. cruzi) infection is a major cause of mortality and morbidity affecting the cardiovascular system for which presently available therapies are largely inadequate. Transforming Growth Factor beta (TGFß) has been involved in several regulatory steps of T. cruzi invasion and in host tissue fibrosis. GW788388 is a new TGFß type I and type II receptor kinase inhibitor that can be orally administered. In the present work, we studied its effects in vivo during the acute phase of experimental Chagas disease. METHODOLOGY/PRINCIPAL FINDINGS: Male Swiss mice were infected intraperitoneally with 10(4) trypomastigotes of T. cruzi (Y strain) and evaluated clinically. We found that this compound given once 3 days post infection (dpi) significantly decreased parasitemia, increased survival, improved cardiac electrical conduction as measured by PR interval in electrocardiography, and restored connexin43 expression. We could further show that cardiac fibrosis development, evaluated by collagen type I and fibronectin expression, could be inhibited by this compound. Interestingly, we further demonstrated that administration of GW788388 at the end of the acute phase (20 dpi) still significantly increased survival and decreased cardiac fibrosis (evaluated by Masson's trichrome staining and collagen type I expression), in a stage when parasite growth is no more central to this event. CONCLUSION/SIGNIFICANCE: This work confirms that inhibition of TGFß signaling pathway can be considered as a potential alternative strategy for the treatment of the symptomatic cardiomyopathy found in the acute and chronic phases of Chagas disease.